Auditory performance in early implanted children with cochleovestibular malformation and cochlear nerve deficiency - Othman, Iylia Ajmal; Abdullah, Asma; Goh, Bee See; Umat, Cila; Tyler, Richard S (AVES, 2020)
OBJECTIVES: This study aimed to report the auditory performance in children with cochleovestibular malformation (CVM)/cochlear nerve deficiency (CND) who were implanted early at the Universiti Kebangsaan Malaysia Medical Centre, using Categorical Auditory Performance (CAP)-II score and Speech Intelligibility Rating (SIR) scales, and to compare the outcome of their matched counterparts. MATERIALS and METHODS: A total of 14 children with CVM/CND with unilateral cochlear implant (CI) implanted before the age of 4 years old were matched and compared with 14 children with normal inner ear structures. Their improvement in auditory performance was evaluated twice using CAP-II score and SIR scales at 6-month intervals, with the baseline evaluation done at least 6 months after implantation. RESULTS: The average age of implantation was 31±8 and 33±7 months for the control group and the case (CVM/CND) group, respectively. Over-all, there were no significant differences in outcome when comparing the entire cohort of case subjects and their matched control subjects in this study. However, the improvement in CAP-II scores and SIR scales among the case subjects in between the first and second evaluations was statistically significant (p=0.040 and p=0.034, respectively). With longer duration of CI usage, children with CVM/CND showed significant speech perception outcome evident by their SIR scales (p=0.011). CONCLUSION: Children with radiographically malformed inner ear structures who were implanted before the age of 4 years have comparable performance to their matched counterparts, evident by their similar improvement of CAP-II scores and SIR scales over time. Hence, this group of children benefited from cochlear implantation